Effect of sonication-assisted cinnamon extract on the physicochemical and quality parameters of fresh-cut carrots (Zoo Botanica, 2025)
The market for minimally processed produce has seen significant growth due to modern lifestyles. However, fresh-cut fruits and vegetables face significant challenges related to quality loss and loss of textural properties. Bioactive coatings are a promising method to lessen these deteriorative effects. This research evaluated the effectiveness of antioxidant-enriched edible coating incorporating sonication-assisted cinnamon extract for preserving the quality of fresh-cut carrots during storage. Cinnamon’s bioactive compounds were obtained via sonication-assisted aqueous extraction. The samples were stored at refrigerated temperature, and quality analyses were performed for a twenty-one-day period. Physicochemical tests included moisture loss percentage, titratable acidity, total soluble solids, texture, color properties, and vitamin C content. Analysis indicated that coated samples demonstrated better retention of quality parameters relative to control samples. Weight loss was slower for treated samples at 20.51% as compared to untreated samples at 19.02%. These findings indicate that antioxidant infused edible coatings could be a viable strategy for prolonging the shelf life of minimally processed food products.
Keywords: Sonication; cinnamon; fresh cut; carrot; edible coating; antioxidants